(untitled) (Castilla. Estudios de Literatura, 2010)
The poems of Adolfo Ares reveal a natural voice, which resonates with the same cosmic rhythm articulated throughout all his writing. From a linguistic point of view, it could be said that his proximity to the spoken word, without which no renewal is possible, enables him to create a dynamic language in a continual process of transformation, through which each poetic experience acquires a new sense. This has been the function of art since antiquity, to locate humanity within the vital rhythm of the universe, which in turn forms the inspiration for all poetry.